A Identification Of Transparency Provision Of Public Infrastructure In Greater Bandung: Identifikasi Transparansi Penyediaan Infrastruktur Publik Di Bandung Raya - Susanto, Wildan Miftah Anugerah; Yustiarini, Dewi (Ikatan Fungsional Pengadaan Indonesia, 2024)
Abstract The public is increasingly feeling the ease of obtaining information in the digital era. With the rise of infrastructure development by the Government, the role of the community as supervisors of development needs to be increased to reduce criminal acts of corruption. Corruption can be reduced if the principle of transparency is implemented. The aim of this research is to determine the information needed by Multistakeholders regarding public infrastructure needs, and to measure the quality of providing infrastructure information as an embodiment of the principle of transparency in the construction services sector in Greater Bandung using the CoST (Construction Sector Transparency) and LPSE (Electronic Procurement Services) Infrastructure Data Standard Instruments. The type of research is qualitative research with a case study method. The results of the research state: 1) The information needed by multi-stakeholders regarding public infrastructure transparency refers to the CoST IDS and LPSE instruments, namely related to project identity, project preparation, project completion, project procurement process, and project implementation, 2) The quality of providing infrastructure information as an embodiment principles of transparency in the construction services sector in Greater Bandung with Infrastructure Data Standard Instruments: a) CoST (Construction Sector Transparency). Measured with 40 questions, an average figure of 64% was obtained, which is in the interval 60.00% - 69.00% (medium category). This indicates that public information providers are available at all times regarding infrastructure information in Greater Bandung, and b) LPSE (Electronic Procurement Services). Measured with 27 questions, an average figure of 72% was obtained. namely in the interval 70.00% - 79.00%. (medium category). This indicates that public information providers are available at all times regarding infrastructure information in Greater Bandung. Keywords: Transparency, Public Infrastructure, Procurement of Goods and Services.